2020
DOI: 10.1631/jzus.b1900312
|View full text |Cite
|
Sign up to set email alerts
|

Role of LINC00152 in non-small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC) accounts for about 85% of all lung cancer cases. The pathogenesis of NSCLC involves complex gene networks that include different types of non-coding RNAs, such as long non-coding RNAs (lncRNAs). The role of lncRNAs in NSCLC is gaining an increasing interest as their function is being explored in various human cancers. Recently, a new oncogenic lncRNA, LINC00152 (cytoskeleton regulator RNA (CYTOR)), has been identified in different tumor types. In NSCLC, the high expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…One previous study investigated the mechanism of CYTOR in the migration and invasion of NSCLC cells and revealed that CYTOR promoted cell proliferation, migration and invasion ability, and induced radioresistance in NSCLC cells ( 50 ). Another study assessed the role of CYTOR in NSCLC, including the cell cycle and apoptosis and found that CYTOR knockdown also promoted cell apoptosis and induced cell cycle arrest in G1 phase ( 12 ). Our group aims to further explore the role of the CYPOR/miR-206/PTMA axis in the malignant behavior of NSCLC cells and cancer metastasis in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One previous study investigated the mechanism of CYTOR in the migration and invasion of NSCLC cells and revealed that CYTOR promoted cell proliferation, migration and invasion ability, and induced radioresistance in NSCLC cells ( 50 ). Another study assessed the role of CYTOR in NSCLC, including the cell cycle and apoptosis and found that CYTOR knockdown also promoted cell apoptosis and induced cell cycle arrest in G1 phase ( 12 ). Our group aims to further explore the role of the CYPOR/miR-206/PTMA axis in the malignant behavior of NSCLC cells and cancer metastasis in the future.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs are the gold standard for cancer diagnosis and prevention due to their wide range of carcinogenic or antitumoral effects on the occurrence and progression of tumors ( 11 ). Initially, the lncRNA cytoskeleton regulator (CYTOR) was documented to be sufficiently expressed in NSCLC and associated with cell biological activities and frustrating survival rates ( 12 ). In addition, CYTOR overexpression is associated with unsatisfactory clinical results and leads to aggravated cancer cellular mobility, aggressiveness and the epithelial-mesenchymal transition (EMT) of neoplasms, including breast cancer, gastric cancer and colon cancer ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, their results indicated that the protein levels of AKT, vimentin, EGFR, fibronectin, and PI3K in cancer cells decrease significantly after downregulation of CYTOR 47 . Hong et al demonstrated that the CYTOR upregulation in peripheral blood samples and tumor tissues is correlated with worse prognosis of NSCLC patients 42 …”
Section: Crndementioning
confidence: 99%
“…Cytoskeleton regulator RNA (CYTOR or LINC00152) is located on chromosome 2 (828 bases pair) and has an oncogenic role and is upregulated in induced cell proliferation, invasion, and migration of several tumor types. 42 Zang et al reported that CYTOR is high expressed in NSCLC tissues and promotes invasion, metastasis, and growth in NSCLC, which could serve as a prognostic factor for NSCLC patients. Interaction of the CYTOR with miR-195 promotes the oncogenic activity of the CYTOR in NSCLC.…”
Section: Cytormentioning
confidence: 99%
See 1 more Smart Citation